Behavioral governance and digital trust: A systematic review of platforms and civility norms - Truong, Thanh Cong; Nguyen, Huy Khang (Journal of Finance - Marketing Research, 2025)
Digital transformation has changed how trust develops in online environments. Traditional trust models fail to explain digital spaces adequately, where behavioral governance mechanisms, codes of conduct, platform design, legal frameworks, and civility norms shape interactions. Nevertheless, empirical evidence examining how these mechanisms systematically influence digital trust remains scattered across disciplines, limiting comprehensive theoretical frameworks. In this study, a systematic review of 47 studies using PRISMA 2020 guidelines identifies three patterns: bidirectional symbiotic relationships between trust and codes of conduct, cultural moderation effects, and platform design architecture influences. Analysis reveals trust operates hierarchically, with platform trust transferring unidirectionally to peer-user trust (effect observed in 67% of platform studies). Cultural contexts fundamentally shape trust formation pathways and code compliance behaviors. Platform design actively cultivates trust rather than passively facilitating communication, while user substitutability determines reliance on individual goodwill versus reputation signals. These findings advance theory by demonstrating that governance mechanisms shape trust through socio-technical interactions fundamentally different from offline contexts. Practically, they inform culturally adaptive platform design strategies and evidence-based policy frameworks for digital civility.